The Phenomenon of Arabic-English Translation of Foreign Language Classes During The Pandemic - Khan, Raja Muhammad Ishtiaq; Kumar, Tribhuwan; Supriyatno, Triyo; Nukapangu, Venkanna (Ijaz Arabi Journal of Arabic Learning, 2021)
The outbreak of the Covid-19 compelled the education sector to teach remotely. This study attempts to investigate the translation strategies used by Arabic-speaking students in EFL Saudi during online learning. The study used a questionnaire to gather the data. The participants of the study were the 120 EFL learners who majored in English at the PSU. The participant's language is Arabic to find the Phenomenon of Arabic-English Translation of Foreign Language. SPSS was used to analyze the data. The findings are encouraging. And supportive for Arabic-English translation of Foreign Language classes in online teaching. Participants used numerous translation strategies during online learning. They expressed a wide range of opinions about translation to help them in the online learning environment. The outcome demonstrates that they feel one must be immersed in an English-speaking environment for some time before thinking fluently in English. The translation was the most often utilized tool by Saudi EFL students to learn English words and phrases, write, and read English during online learning. The translation had no negative impact on participants' EFL learning. Arabic-English Translation helped in the comprehension of the subject as it is lareners’ mother tongue. Also, it is supported tremendously in EFL learning